2015
DOI: 10.1371/journal.pone.0138500
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Microbubble Size on Ultrasound-Induced Transdermal Delivery of High-Molecular-Weight Drugs

Abstract: The transdermal delivery of a wide range of high-molecular-weight drugs is limited by the stratum corneum layer of the epidermis representing a significant barrier to penetration across the skin. This study first determined the different effects of different-size ultrasound (US) contrast agents and microbubbles (MBs) for enhancing the transdermal delivery of high-molecular-weight drugs. The effects of US-mediated different-size (1.4, 2.1, and 3.5 μm) MBs (as a contrast agent) and ascorbyl tetraisopalmitate (VC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
30
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 27 publications
0
30
0
Order By: Relevance
“…Molecular size and shape The molecular weight of a chemical is a good indicator of its molecular size, which, in turn, is related to the diffusion coefficient according to the Stokes-Einstein relation. As drug diffusion through the skin is a passive mechanism, small molecules traverse the human skin faster than larger molecules [15]. Therefore, candidates for transdermal delivery should have a molecular weight not higher than 500 Dalton.…”
Section: Formulation Related Factors Temperature and Phmentioning
confidence: 99%
“…Molecular size and shape The molecular weight of a chemical is a good indicator of its molecular size, which, in turn, is related to the diffusion coefficient according to the Stokes-Einstein relation. As drug diffusion through the skin is a passive mechanism, small molecules traverse the human skin faster than larger molecules [15]. Therefore, candidates for transdermal delivery should have a molecular weight not higher than 500 Dalton.…”
Section: Formulation Related Factors Temperature and Phmentioning
confidence: 99%
“…2 Transdermal drug delivery offers several advantages to address issues associated with oral delivery and hypodermic injections through the application of specialized medicated adhesive patches onto the skin. 3 However, there are several limitations associated with transdermal drug delivery systems. The efficacy and implementation of transdermal drug delivery is principally limited by the physical barrier of the skin.…”
Section: Introductionmentioning
confidence: 99%
“…A previous study demonstrated that US-assisted vaccine delivery in the presence of sub-micron cavitation nuclei resulted higher specific antibody levels compared to other transdermal methods 14 . Our previous studies demonstrated that combined treatment with US using optimal parameters and optimal conditions (size or concentration) of microbubbles (MBs) can increase skin permeability so as to enhance drug delivery without increasing temperatures or causing heating damage 15,16 . Minoxidil (Mx)-coated albumin-shelled MBs produced in a layer-by-layer manner combined with sonication by US energy in the water phase successively enhanced hair growth while shortening the treatment period 17 .…”
mentioning
confidence: 99%